2019
DOI: 10.4103/sjamf.sjamf_50_19
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte disturbances in patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: Introduction Chronic obstructive pulmonary disease (COPD) is a cover term that includes a variety of progressively debilitating lung diseases. COPD includes both emphysema and chronic bronchitis. Although COPD is mainly a chronic disease, a substantial number of patients experience exacerbations that are related to a significantly worse survival outcome, especially with abnormal serum electrolyte level. Aim To detect the serum electrolytes disturbances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Hypokalemia was found in 104 (86.67%) patients, hypocalcemia in 95 (79%), hypochloremia in 95 (79%) patients, and hyponatremia in 76 (63%) patients. This agrees with another study [ 9 ] that measured the serum potassium and sodium in 64 patients with COPD and compared the results with 20 healthy volunteers. This study found a significant decrease in serum levels of K + (3.39±0.96 mEq/L) and Na + (133±6.86 mEq/L) in COPD patients when compared to the control groups (4.52±0.02 mEq/L, 142±2.28 mEq/L, respectively, P<0.05).…”
Section: Discussionsupporting
confidence: 89%
“…Hypokalemia was found in 104 (86.67%) patients, hypocalcemia in 95 (79%), hypochloremia in 95 (79%) patients, and hyponatremia in 76 (63%) patients. This agrees with another study [ 9 ] that measured the serum potassium and sodium in 64 patients with COPD and compared the results with 20 healthy volunteers. This study found a significant decrease in serum levels of K + (3.39±0.96 mEq/L) and Na + (133±6.86 mEq/L) in COPD patients when compared to the control groups (4.52±0.02 mEq/L, 142±2.28 mEq/L, respectively, P<0.05).…”
Section: Discussionsupporting
confidence: 89%
“…Similar finding was found in the study conducted in Egypt which showed that (58.5%) patients had electrolyte disorder. 13 It was found that 51% patients had hyponatremia and 49% had normal level of sodium. Likewise, 40% patients had hypokalaemia and 2% had hyperkalemia and more than half (58%) were in normal range.…”
Section: Discussionmentioning
confidence: 98%
“…Hyponatremia is a common electrolyte disorder that develops frequently in 15–40% of hospitalised patients. 23 Hyponatremia during infection may be transient and may be overlooked by clinicians as it did not lead to specific manifestations. Nonetheless, hyponatremia in infections indicated underlying disease severity and is linked to delayed hospitalization and significant morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, hyponatremia in infections indicated underlying disease severity and is linked to delayed hospitalization and significant morbidity. 23 In the majority of cases, causes of hyponatremia are multifactorial. However, increased levels of antidiuretic hormone (ADH), which can be either appropriate, in cases of volume depletion, or inappropriate in cases of inappropriate ADH secretion (SIADH), play the most important role in hyponatremia occurrence in infectious diseases.…”
Section: Discussionmentioning
confidence: 99%